Izolovaná leukemická infiltrace duhovky - Hejcmanová, D; Jebavá, R; Hak, J; Slavík, Z; Vanásek, J; Simáková, E (Ceskoslovenska oftalmologie, 1993)
A boy 3 1/2 years old with the diagnosis acute lymphoblastic leukemia, in stage of high malignity, came to the Eye clinic in Hradec Králové. The clinical and haematological findings showed the remission of the illness but a leukemic infiltration with hypopyon had arised. The diagnosis has been done selon the clinic image of the eye and selon the ultrasound examination. The histologic finding showed also an infiltration of chorioidea, iris and ciliary body, an infiltration in the nuchal region, in the spleen and in testicles. The isolated leukemic infiltration of the iris can be the first sign of a relapse and is an indication to begin a relevant therapy.
Keywords: mužské pohlaví; akutní lymfatická leukemie; leukemická infiltrace; iris; Male; lidé; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Iris; Leukemic Infiltration; předškolní dítě; Child, Preschool